Dark septate endophytes symbiosis in Falcataria moluccana and its potency for forest and landscape restoration - Surono .; Yulianti .; K.P. Putri; D.J. Sudrajat; Y.M.M.A. Nugraheni; C. Sriherwanto; M.A. Syabana; N. Widyani; N. Yuniarti; M. Zanzibar; E. Rustam; R.U.D. Sianturi (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Falcataria moluccana is a potential forest tree species with high economic value in Indonesia, and it is widely planted in various forests and landscape restorations. F. moluccana planting has declined in productivity due to decreased site quality and pest and disease attacks. Dark septate endophytes are a group of root endophytic fungi that have potential as biological control and promoter agents. This research aims to test the symbiotic potential of several dark septate endophytes isolates, to determine the effect of dark septate endophytes on the germination of F. moluccana seeds, and what types of secondary metabolites are produced from this symbiotic interaction. METHODS: Three dark septate endophytes isolates, i.e., Rhizopycnis vagum, Curvularia sp., and Dendrothyrium sp. were used in this study. Those isolates were inoculated on the seeds of F. moluccana and observed the endophytism and metabolite compounds produced after 23 hours and 14 days of inoculation time.FINDINGS: Three new findings of this study were: 1) the dark septate endophytes isolates, i.e., Rhizopycnis vagum, Curvularia sp., and Dendrothyrium sp. could colonize F. moluccana seeds on the surface with a colonization rate of 96 percent, 32.5 percent, and 100 percent, and entered the seed tissue and the sprout roots with a colonization rate of 93.3 percent, 93.3 percent, and 70 percent. The dark septate endophytes colonization could be seen at the beginning of germination, inoculation of 0-23 hours, and after germination until observation at the age of 14 days; 2) The dark septate endophytes has the potential to improve seed germination and vigor of F. moluccana, by speeding up the germination process and increasing the vigor index, this condition is expected to produce seeds that can grow and survive environmental stress; 3) The dark septate endophytes has the potential to trigger an increase secondary metabolite compounds in F. moluccana seeds, which can be as antibacterial, antifungal, and antioxidants such as the Hexamethyl Cyclotrisilaxane compound, 1-Isopropenyl-4-methyl-1,3-cyclohexadiene, and Acetamide, 2, 2,2-trifluoro-N-methyl-N- (trimethylsilyl) as a form of plant protection when the F. moluccana seeds grew and developed to be a normal seedling. These conditions are believed to produce high-quality seedlings that can grow and adapt well to their new environment after being outplanted.  CONCLUSION: Dark septate endophytes colonization of F. moluccana seeds does not reduce seed viability, so dark septate endophytes inoculation of seeds can be used as a seed treatment and can produce healthy and vigorous F. moluccana seedlings, thereby increasing the success of planting in the context of restoration of degraded forest and landscape.